1993
DOI: 10.1093/schbul/19.1.141
|View full text |Cite
|
Sign up to set email alerts
|

The New York High-risk Project: Anhedonia, Attentional Deviance, and Psychopathology

Abstract: In the New York High-Risk Project (NYHRP) we followed subjects at risk for schizophrenic or affective disorders and low-risk controls from childhood to adulthood, with the goal of identifying early predictors of later schizophrenia-related psychopathology. In this article, we focus on two potential predictors: the Physical Anhedonia Scale administered in adolescence and the Attention Deviance Index obtained in childhood. Subjects of this report are 161 members of the NYHRP's first sample (sample A), who had sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
71
0
3

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(80 citation statements)
references
References 46 publications
5
71
0
3
Order By: Relevance
“…Though the striatum is thought to be a critical region for DA dysfunction in schizophrenia, there may also be differences in frontal cortical DA systems that our method could not detect. Third, although our particular interest is in schizophrenia vulnerability, our personality measures of vulnerability are sensitive to risk for psychosis, including affective psychosis (Erlenmeyer-Kimling et al, 1993;Chapman et al, 1994). Increased DA release in response to stress may represent a risk factor for psychosis in general, rather than a risk factor for schizophrenia per se (Yui et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Though the striatum is thought to be a critical region for DA dysfunction in schizophrenia, there may also be differences in frontal cortical DA systems that our method could not detect. Third, although our particular interest is in schizophrenia vulnerability, our personality measures of vulnerability are sensitive to risk for psychosis, including affective psychosis (Erlenmeyer-Kimling et al, 1993;Chapman et al, 1994). Increased DA release in response to stress may represent a risk factor for psychosis in general, rather than a risk factor for schizophrenia per se (Yui et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with elevated scores on the PerAb scale have an elevated risk of psychosis (Chapman et al, 1980(Chapman et al, , 1994, an elevated rate of schizophrenia in first-degree relatives (Lenzenweger and Loranger, 1989) and a myriad of cognitive and psychophysiological deficits that are associated with schizophrenia (Simons, 1982;Allen et al, 1987;Jutai, 1989;Lenzenweger, 1991;Simons and Giardina, 1992;Kwapil et al, 1996;Suhr, 1997;Nuchpongsai et al, 1999;Gooding et al, 2001). Elevated PhysAn scores in the adolescent offspring of schizophrenic patients are associated with increased rates of psychosis and poorer social adjustment in young adulthood (Erlenmeyer-Kimling et al, 1993;Freedman et al, 1998). Healthy individuals with elevated scores on the PhysAn scale also show many attributes of a high-risk population: they have an increased incidence of the cognitive, behavioral, and social abnormalities associated with schizophrenia, including impaired attention (Jutai, 1989;Wilkins and Venables, 1992;Erlenmeyer-Kimling et al, 1993), reaction time crossover (Simons, 1982), abnormal P300 amplitude (Miller, 1986), skin conductance nonresponsiveness (Dawson and Nuechterlein, 1984), and poorer social competence (Garnet et al, 1993;Blanchard et al, 1998).…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…42 The reason among the offspring of schizophrenic parents. 19 Two more recent prospective studies of large birth cohorts is that in the former case many markers are assayed simultaneously and in principle compete with one designed to address and test this prediction 20,21 found that patients destined to develop schizophrenia another, whereas in the latter case only one marker is being assayed (that marker previously implicated showed (as early as at the age of 4) significant deficits in a range of behaviors compared to their peers: solitary in an independent linkage study). play, reduced educational achievement, more anxiety, poor speech development and poor motor control.…”
Section: Introductionmentioning
confidence: 99%